Prognostic impact of residual disease in simultaneous additional excision specimens after one-step breast conserving therapy with negative final margin status in primary breast cancer. Issue 9 (September 2018) - Kahlert, Steffen; Kolben, Theresa M.; Schmoeckel, Elisa; Czogalla, Bastian; Hester, Anna; Degenhardt, Tom; Kempf, Cordula; Mahner, Sven; Harbeck, Nadia; Kolben, Thomas
Abstract: Purpose: The purpose of this study was the evaluation of risk factors for local recurrence after breast conserving surgery (BCS) with special focus on the impact of residual disease in specimens of simultaneous additional excisions (AE) from the tumor cavity on patients' outcome in patients with negative final margin status after one-step BCS. Methods: This study was designed as a single center retrospective cohort study. Patients with primary non-metastatic breast cancer treated by one-step BCS with pathologically confirmed negative resection status between 1990 and 2006 were included. Ipsilateral breast tumor recurrence (IBTR) and overall survival (OS) were evaluated by Kaplan-Meier-estimates. A multivariate Cox proportional hazards regression model was used to identify potential independent prognostic factors associated with the risk of IBTR. Results: A total of 1081 patients were included in this analysis. Simultaneous additional excisions were performed in 79.4% of patients (tumor positive: 12.2%). Median follow-up after primary diagnosis was 124 months. The IBTR rate after 15 years was significantly higher in the group with tumor positive AE (no AE (10.2%) vs. AE tumor positive (27.5%) p = 0.002; AE tumor negative (14.0%) vs. AE tumor positive (27.5%) p = 0.008). The OS rate did not differ significantly between groups. Multivariate analysis revealed residual cancer in AE being associated with a significantly increased relative risk of IBTR of 2.0 (p = 0.014). Conclusion: In the current analysis residual disease in simultaneous additional excisions was associated with an increased risk for IBTR despite negative final margin status. This should be considered in the overall therapeutic concept.